2013
DOI: 10.1155/2013/851256
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Mechanism of Cinobufagin in the Treatment of Paw Cancer Pain by Modulating Localβ-Endorphin ExpressionIn Vivo

Abstract: Background. Cinobufagin has been widely used in the treatment of carcinoma and plays an important role in the relief of cancer pain. But the involved mechanism remains unknown. Aim. To investigate the changes in thermal and mechanical hyperalgesia in paw cancer pain in mice and the action mechanism of cinobufagin using a paw cancer pain model. Methods. 60 female mice were randomly divided into 5 groups: control group, model group, cinobufagin group, cinobufagin +NAL-M group, and morphine group; except ones in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
2
26
1
Order By: Relevance
“…Moreover, the antinociceptive effect of Bufonis venenum or bufalin was blocked by the pretreatment with the opioid receptor antagonist naloxone or its peripheral form naloxone methiodide [9,10,74]. These studies suggested that Bufonis venenum and its effective ingredients produced antinociception through the β-endorphin/opioid receptor pathway [9,10].…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Moreover, the antinociceptive effect of Bufonis venenum or bufalin was blocked by the pretreatment with the opioid receptor antagonist naloxone or its peripheral form naloxone methiodide [9,10,74]. These studies suggested that Bufonis venenum and its effective ingredients produced antinociception through the β-endorphin/opioid receptor pathway [9,10].…”
Section: Introductionmentioning
confidence: 93%
“…The CRF receptor was associated with microglial expression of β-endorphin [8,33,40] and Bufonis venenum stimulated CRF expression [9,10]. Thus, the possible involvement of the CRF receptor in cinobufagin-induced mechanical antiallodynia was finally tested.…”
Section: Activation Of the α7-nachr Mediated Cinobufagininduced Spinamentioning
confidence: 99%
See 3 more Smart Citations